أهمية العقل البشري في القران الكريم - عكاب, حيدر خزعل فهد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The emphasis of the Holy Qur'an on the importance of reason in many verses shows that the success of man in all areas of life can only be achieved through the knowledge and guidance of the Holy Qur'an، and the Qur'an rules on the legality and illegitimacy of human possessions based on the submission of the human mind to legislation and regulation of life. God's law، yes، it is a modification of all the previous divine laws. And it includes the foundations of laws and regulations، including laws that agree with the human mind and are in accordance with maturity (The duty of the law: planning and planning، stating the general principles and general rules، and allowing the rational mind to legislate laws in the light of those bases and rules and not to deviate from them. Also، the Qur'an is a divine command، limited to the general principles. ، and the universal fixed rules، and the human intellect returns the details to those universals in all time and space in the light of the requirements of life، and establishes the framework of ethics، and he said to the human intellect، movement to create us precedes man، and it evolves into life from the best to the best، as long as this movement is Within this framework of ethics)). After discussing this place of reason in the Qur'an، there comes the stage of the interaction of reason in it as a religious obligation. The Holy Quran's address to reason in this gradual way shows that the practice of reason is a duty، because it is the scale that weighs right and wrong، and truth and falsehood، and to the realization of God's end. I am the creator of mankind، the Most High said (Al-Rahman. All-Mighty. All-Mighty. All-Mighty-All-Bayyan)) So the practice of the mind is the duty of the duty، that is، all the duties are not fulfilled except by the duty of the application of the mind in the required form.